Explaining Growing Glyphosate Use: The Political Economy of Herbicide-Dependent Agriculture. (March 2021) - Clapp, Jennifer
Highlights: Global glyphosate use in agriculture has increased sharply since the 1980s. There are growing concerns about the environment and human health implications of glyphosate. A complex interplay of technology, market and regulatory forces encouraged expansion of glyphosate use. Four distinct yet overlapping configurations of these forces have emerged since the 1980s. Abstract: The growing use of chemical herbicides for weed control has become a dominant feature of modern industrial agriculture and a major environmental and health concern in agricultural systems worldwide. This paper seeks to explain how and why glyphosate-based agricultural herbicides have become so entrenched in modern agriculture. It shows that a complex interplay among technological, market, and regulatory developments have encouraged a lock-in of glyphosate linked technologies in agricultural systems. These are: (1) the repurposing of glyphosate for use with genetically modified crops; (2) the rise of the generic glyphosate market, which globalized the chemical's use and encouraged new agricultural uses; (3) new technologies such as digital agriculture and genome editing that interface with glyphosate use; and (4) growing corporate market power and declining public investment in agricultural research programs that constrained innovation in non-herbicide weed control technologies.